PERANAN EKOLOGI DUSUNG DAN NON DUSUNG DAN KONTRIBUSINYA PADA KONSERVASI LINGKUNGAN DI DESA URENG KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Napsiah Heluth; J. Matinahoru; Fransina Latumahina (JURNAL HUTAN PULAU-PULAU KECIL, 2018)
The research study aims to determine the ecological conditions of dusung and non dusung, and the role of the contribution to environmental conservation in Ureng Village. The research method used was purposive sampling with observation parameters were microclimate (CO2 content, air temperature, humidity), vegetation conditions and soil conditions (soil temperature, soil moisture, soil pH, soil moisture content, soil macrofauna and organic C) . The results of Paired of each parameter measured mostly show a smaller calculated t value compared to the t0.05 table value (1.8595) which means that the parameter is not a real difference, ie for the air humidity, t count = 0.27,; soil pH, t count = 0.6; soil macrofauna, t count = -0.66 and vegetation, t count = 1.01. As for the parameters of CO2; air temperature, soil temperature, , soil water content and organic C, t value of CO2 gives the value t count = - 16.06; air temperature = -5.11; soil temperature = -3.62; soil moisture, t count = 2,16; soil water content = 8.47, and C-Organic = 8.53; t count value which is greater than t table value which shows that there is a significant difference between CO2, air temperature, soil temperature, soil moisture, soil water content and C-Organic content in the dusung area which is greater than in the non-dusung area. From the results of the analysis it is known that dusung has a better role in environmental conservation when compared to non dusung which is indicated by the value of CO2 air temperature, soil temperature, soil moisture, soil water content and C-organic content.